The tattoo environment as a therapeutic healing space for sexual assault survivors - Maxwell, December (Deviant behavior, 2024)
The view of tattoos and the tattooed is emerging from a position of deviance and criminology to a potential practice for restoration and healing. Tattooing is emerging as a process through which survivors of sexual trauma can reclaim bodily autonomy after experiencing violation. Additionally, the opportunity for the tattooing environment to be a healing space is emerging. Through the application of the theory of supportive care environments, this study sought to better understand how the tattoo environment operated as a therapeutic healing space by conducting a secondary data analysis on qualitative interviews conducted with ten survivors of sexual trauma and seven tattoo artists. Results highlight the importance of aesthetic of the space which contribute to it being perceived as comfortable and safe, experiencing a sense of belonging within the safe both in the rapport built between the artist and client and in the ritual of receiving a tattoo, and in the empowerment of the individual receiving the tattoo to exercise their autonomy within the tattooing space. Results implicate the ability of the tattooing space to be a trauma-informed, healing environment and point to the importance of incorporating ritual and spirituality into the healing process for survivors of sexual trauma.